Multicriteria Decision Model for Road Construction Project - SN, Ramlay; Putri Zulaiha, Razi; Mohamad Idris, Ali; Noram Irwan, Ramli; MSH, Saad; O, Jamaludin; Doh, Shu Ing (IOP Publishing Ltd, 2023)
. Construction of roads plays an important role in linking one area to another, and also acts as a substance for the local economy. However, the limitation of study on the project performance towards the road infrastructure construction project requires more precise attention. Thus, it requires distinct responsiveness from contractors to evaluate and cope with the risks. This study aims to identify the project execution risk factors involved in the road construction project, reference to a current case study from a federal government project Public Work Department (PWD) on the East Coast of Malaysia: Upgrading 14.7 kilometre (km) federal road from the Pekan town to Sungai Miang. This study will begin with the identification of the project execution risk factors, utilizing an extensive review of the literature. Next, the gathered risk factors will go through a pilot phase validation interview with road construction experts from the public work department (PWD) and also construction practitioners that are involved directly in the project case study. Findings found seven (7) main project execution risk factors involved in the road construction project, which include resource risk, land acquisition issue, project management issue, technical risk, service utility issue, unforeseen ground condition, and force majeure risk. Among the seven (7) factors twenty-one (21) project execution risk sub-factors, were further explored that are crucial to the project. The main contribution of this study is the final multi-criteria decision model obtained from literature searching cross-referenced to the real case study that may be beneficial to the road construction project team specifically.